Acetylsalicylic acid use and development of cardiac allograft vasculopathy: A national prospective study using highly automated 3-D optical coherence tomography analysis - Mayerova, Lucie; Wohlfahrt, Peter; Sonka, Milan; Chen, Zhi; Kautzner, Josef; Melenovsky, Vojtech; Karmazin, Vladimir; Malek, Ivan; Bedanova, Helena; Tomasek, Ales; Ozabalova, Eva; Krejci, Jan; et al. (Clinical transplantation, 2024)
BACKGROUND: There is conflicting evidence on the role of acetylsalicylic acid (ASA) use in the development of cardiac allograft vasculopathy (CAV). METHODS: A nationwide prospective two-center study investigated changes in the coronary artery vasculature by highly automated 3-D optical coherence tomography (OCT) analysis at 1 month and 12 months after heart transplant (HTx). The influence of ASA use on coronary artery microvascular changes was analyzed in the overall study cohort and after propensity score matching for selected clinical CAV risk factors. RESULTS: In total, 175 patients (mean age 52 ± 12 years, 79% male) were recruited. During the 1-year follow-up, both intimal and media thickness progressed, with ASA having no effect on its progression. However, detailed OCT analysis revealed that ASA use was associated with a lower increase in lipid plaque (LP) burden (p = .013), while it did not affect the other observed pathologies. Propensity score matching of 120 patients (60 patient pairs) showed similar results, with ASA use associated with lower progression of LPs (p = .002), while having no impact on layered fibrotic plaque (p = .224), calcification (p = .231), macrophage infiltration (p = .197), or the absolute coronary artery risk score (p = .277). According to Kaplan-Meier analysis, ASA use was not associated with a significant difference in survival (p = .699) CONCLUSION: This study showed a benefit of early ASA use after HTx on LP progression. However, ASA use did not have any impact on the progression of other OCT-observed pathologies or long-term survival.
Keywords: optická koherentní tomografie; Heart Transplantation; Male; Coronary Artery Disease; lipid plaque; Adult; alografty; Prospective Studies; dospělí; mužské pohlaví; Coronary Angiography; acetylsalicylic acid; nemoci koronárních tepen; transplantace srdce; OCT; lidé; ženské pohlaví; Humans; Tomography, Optical Coherence; koronární angiografie; Allografts; cardiac allograft vasculopathy; aterosklerotický plát; Female; lidé středního věku; Plaque, Atherosclerotic; Middle Aged; prospektivní studie